Why things look the way they do: we live in a Cartesian grid of reified concepts - Brown, Guy C. (Frontiers in Psychology, 2025)
The world we live in now is almost exclusively populated by things designed by minds to be understood by other minds. I argue here that: (1) Human environments now consist mainly of reified concepts, such as “chairs.” (2) These externalized concepts look like simple cartoons of the concepts they reify, with flat, homogenous surfaces in geometric shapes, with one or a small number of colors, textures and surfaces, so that they can be easily identified and distinguished. (3) Reified concepts are organized within a Cartesian grid, that enables their perception, location and memory. (4) Simple concepts are nested within complex concepts, such as rooms, houses, streets, hospitals or cities, designed to be read by our minds, and guide behavior, within the externalized mind of society. (5) Components of the human environment that are not conceptual are actively removed, resulting in a very low entropy of information, and giving the illusion that reality is entirely conceptual. (6) Reified concepts and their conceptual ordering help perception, comprehension and use of human environments. (7) These ideas have application to design, architecture, aesthetics, phenomenology, ontology and understanding why things look the way they do.